ДИСКОВЫЙ ЭЛЕКТРОДВИГАТЕЛЬ С ПОСТОЯННЫМИ МАГНИТАМИ ДЛЯ КОМБИНИРОВАННОГО ПРИВОДА МЕХАНИЗАЦИИ КРЫЛА САМОЛЕТА - Гребеников, В.В.; Прыймак, М.В.; Гамалея, Р.Р.; Шарабан, Ю.В. (Інститут електродинаміки НАН України, Київ, 2015)
In this article, we consider an integrated approach to design of disc-type motor with permanent magnets on the rotor. As the design object an electric motor is selected and intended for use as a drive of mechanization of a wing in airplane An-178. This approach involves the selection of number for poles, preliminary optimization of the magnetic system in Comsol Multiphisics package with the wiev of obtaining maximum static torque at the given overall dimensions of electric machine, the estimation of loss on heating and eddy currents, as well as calculation of the dynamics motor mode using Matlab Simulink package and building the motor load characteristic. References 4, figures 8.